Lives and livelihoods on the streets of Dhaka city: findings from a population-based exploratory survey - Ahmed, Syed Masud; Hossain, Shamim; Khan, Antora Mahmud; Islam, Qazi Shafayetul; Kamruzzaman, Md. (BRAC, 2019)
BRAC has long been working to empower people and communities in situations of poverty, illiteracy, disease and social injustice. In recent years, BRAC has extended its activities to include the urban poor population living in the slums. As a continuation of this, and to be more inclusive, BRAC is going to implement innovative programmes for the street dwellers (who sleep on streets, railway terminals and platforms, bus stations, parks and open spaces, religious centres, construction sites and around graveyards and in other public places with no room in scale. BRAC Research and Evaluation Division carried out an exploratory cross-sectional survey on a sample of these populations from 10 purposely selected areas of Dhaka city to gather information on their lives and livelihoods, using both quantitative and qualitative methods. Findings reveal that the street dwellers (driven by poverty and natural disasters) had to adopt a very precarious and humiliating life on the streets devoid of all basic amenities of life, under constant threat of eviction and harassment by the law-enforcing agencies and hoodlums. They were hard-working when considered in terms of working hours, but without proportionate return due to their involvement in low paying informal sector which is also irregular. They failed to improve their lot even after five or more years of street-living. According to them housing, food, and lack of jobs were the three most common problems for which they sought assistance. The implication of these findings for programme development is discussed.